Managing controversies when advertising underwear on social media - Brites, Filipa Marques Costa do Amaral (2022)
The following dissertation will explore the brand’s communication strategies to manage the inherent controversy of advertising women's underwear, especially lingerie and swimwear, on social media. Previous research advocated the social media's effect on fashion brands and consumer behavior. However, the underwear’s research is very limited, being mainly related to its history and impact on consumers’ identity, opening an opportunity to study the underwear brands/social media’s relationship deeply. A qualitative approach was chosen, and four underwear brands were deeply analyzed to proceed with this study. This thesis’ findings evidence the existence of four major challenges: 1) Managing paradoxes of communicating intimate products, 2) Managing social media communication paradoxes; 3) Managing social pressure and lastly, 4) Managing the possibility of being wrongly interpreted. Additionally, some strategies were pointed out to face the previous challenges. Although, all these strategies contribute to these brands’ common goal of establishing a solid connection with audiences. These brands believe that the better the relationship with the audience, the easier the management of underwear controversies on social media will be. This strategy constitutes the way of managing the underwear’s controversies when advertising on social media. This study's relevancy is unquestionable for underwear advertisers and for the overall fashion industry since some communication paradoxes can be transposed to other fashion fields.